Navigating Gendered Space with Special Reference to Lil Bahadur Chettri’s Mountains Painted with Turmeric - Swain, Tamishra; Shah, Shalini (Bodhi: An Interdisciplinary Journal, 2019)
It is rightly put by the French philosopher Simone De Beauvoir in her book ‘Second Sex’ that “one is not born but made a woman”. So, women are treated secondary as compared to men for a long time. Similar view has been propounded by Judith Butler in her book ‘Gender Trouble’ that female identity has been created by repetitive performances and further, gender identity is not fixed rather it is created. There are certain agencies through which these ideologies came in to function. One of such agencies is “space” which is not necessarily physical and fixed but can be mental/psychological and fluid. This space can also use as subversive technique to control certain part of the society. This paper tries to analyze a Nepali fiction ‘Mountains Painted with Turmeric’ by Lil Bahadur Chettri to understand the subversive practices of space and how it controls gender identity.